Implementasi Manajemen Pengetahuan pada Perguruan Tinggi Swasta di Kabupaten Garut - Hendarsita Amartiwi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2019)
This study scrutinize the factors affecting knowledge management, consisting of acquisition of knowledge, storage of knowledge, distribution of knowledge and use of knowledge, at Private Higher Education Institutions in Garut Regency.Â  The purpose of this study is to analyze the factors shaping the knowledge management.Â  By using a survey method with a quantitative approach, the unit of analysis of this study is lecturer at 14 Private Universities in Garut Regency, with 229 lecturers as respondents. Data is obtained from survey results through questionnaires distributed directly to lecturers. Data is processed using descriptive statistical analysis and Confirmatory Factor Analysis (CFA). The research findings showed that the use of knowledge and the storage of knowledge are the most powerful factors in knowledge management, followed by the acquisition of knowledge, and distribution of knowledge.